Development of Teachers’ Potential and Educational Personnel in Term of Authentic Assessment - Krapan Sri-ngan; Suchart Homjan (Journal of Educational Issues, 2024)
The objective of this research was to develop teachers’ potential and educational personnel in term of authentic assessment under the Buriram Primary Educational Service Area Office 2 by using 2 cycles of action research. Each cycle included planning, action, observation and reflection. The research group consisted of 10 people, the target group was 36 people, and the group of additional information providers was 25 people. The research instruments were test, observation form, interview form, and record form (Triangulation) and presented the results of descriptive studies. The results showed that in the development of teachers and educational personnel in the first cycle used brainstorming strategies by a way of sharing opinions on the process of finding ideas and ways to solve the similar problem together, strategies for training workshops by using a lecture method to provide knowledge based on the content framework, practical training, consulting advice, questioning and participatory supervision strategies by observing teaching methods. This enabled personnel to have more knowledge and understanding of principles, procedures, and methods of measurement and evaluation based on authentic assessment. They were able to create authentic measurement and evaluation instruments and had the ability to measure and evaluate results based on authentic assessment by using a variety of measurement and evaluation methods. Most of the students cooperated in the activities but there were still some steps that the target group was unable to complete, that was the students had few activities and some target groups gave students less opportunity for self-report and self-assessment. Therefore, the development was carried out in the second cycle by using participatory supervision strategies by observing teaching methods. This enabled all personnel to have knowledge and understanding of the measurement and evaluation process, determined methods for measuring and evaluating according to authentic assessment, selected the correct evaluation methods according to the content. Measurement and evaluation with emphasizing on practicality and being able to measure and evaluate according to authentic assessment for teaching and learning. Most of the students participated in more activities and the measurement and evaluation based on authentic assessment.